Pengaruh Pengembangan Karir Terhadap Kinerja Pegawai Di Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Nurani Magfirah Enggowa; Welson Yappi Rompas; Novva Novita Plangiten (Sam Ratulangi University, 2023)
ABSRACT This study aims to determine the effect of career development on employee performance in the Regional Education Office of North Sulawesi. The study employs a survey method, which draw a sample from a population an uses a data-collecting apparatus. The design of this survey method is a quantitative description. The data processed was the result of the distribution of questionnaires to civil servants of the Regional Education Office of North Sulawesi with a population of 155 people and a sample of 62 respondents. This study used a simple linear regression analysis technique. The results obtained show that there is a positive influence between career development on employee performance, this means that the better the application of career development, the better the employee's performance will be. Keywords : Career Development, Employee Performance